Antarctic Zone nutrient conditions during the last two glacial cycles. (14th July 2015) - Studer, Anja S.; Sigman, Daniel M.; Martínez‐García, Alfredo; Benz, Verena; Winckler, Gisela; Kuhn, Gerhard; Esper, Oliver; Lamy, Frank; Jaccard, Samuel L.; Wacker, Lukas; Oleynik, Sergey; Gersonde, Rainer; et al.
Abstract In a sediment core from the Pacific sector of the Antarctic Zone (AZ) of the Southern Ocean, we report diatom‐bound N isotope (δ15Ndb) records for total recoverable diatoms and two distinct diatom assemblages (pennate and centric rich). These data indicate tight coupling between the degree of nitrate consumption and Antarctic climate across the last two glacial cycles, with δ15Ndb (and thus the degree of nitrate consumption) increasing at each major Antarctic cooling event. Coupled with evidence from opal‐ and barium‐based proxies for reduced export production during ice ages, the δ15Ndb increases point to ice age reductions in the supply of deep ocean‐sourced nitrate to the AZ surface. The two diatom assemblages and species abundance data indicate that the δ15Ndb changes are not the result of changing species composition. The pennate and centric assemblage δ15Ndb records indicate similar changes but with a significant decline in their difference during peak ice ages. A tentative seasonality‐based interpretation of the centric‐to‐pennate δ15Ndb difference suggests that late summer surface waters became nitrate free during the peak glacials.